2006
DOI: 10.3164/jcbn.39.162
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modulating Effects of Daily Supplementation of COLD-fX (a Proprietary Extract of North American Ginseng) in Healthy Adults

Abstract: In a previous study, COLD-fX (CVT-E002), a proprietary extract of the root of North American ginseng (Panax quinuefolium), was found effective in the prevention of upper respiratory tract infections (URIs) in healthy adults. The underlying mechanisms of its action, however, were not determined. The present study was carried out to explore if the effects observed could be due to COLD-fX-mediated changes in the distribution of peripheral blood leukocytes, changes in the relative distribution of lymphocyte subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…AGRPS and AQ extracts are not antagonists of LPS because they have low stimulatory effect and also requires pretreatment before they can suppress LPS stimulation. The data from this study supports the reported CVT-E002 TM immunostimulatory [22,29,48,[59][60][61][62] and suppression of proinflammatory effects [21,63] under basal and induced proinflammatory conditions respectively. Therapies directed at the neutralization of proinflammatory mediators Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…AGRPS and AQ extracts are not antagonists of LPS because they have low stimulatory effect and also requires pretreatment before they can suppress LPS stimulation. The data from this study supports the reported CVT-E002 TM immunostimulatory [22,29,48,[59][60][61][62] and suppression of proinflammatory effects [21,63] under basal and induced proinflammatory conditions respectively. Therapies directed at the neutralization of proinflammatory mediators Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The ex vivo, in vivo and in vitro studies support the observations from our previous study, indicating that bioactive AGRPS isolated from AQ extract and its parent AQ extract exerted immunostimulatory effects [32]. The in vivo immunostimulatory effect of 125 mg/kg AGRPS and AQ extracts was very small as compared with 5 mg/kg LPS toxic stimulatory effect, suggesting that American ginseng extract and its natural health product containing polysaccharides like CVT-E002™ are safe with health benefits with regards to immunostimulation [48]. The results from this study suggests that under LPS mediated excessive stimulatory infectious condition like endotoxemia; pretreatment with AGRPS and AQ extracts will not cause additive immunostimulatory effects, but rather the extracts will reduce and neutralize LPS immunologic stimulatory effect.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…And a few polysaccharides, including lentinan, Astragalus polysaccharide, polyporus polysaccharide and Achyranthes bidentata polysaccharide have been licensed for clinical application in China [16]. In Canada, a polysaccharide-enriched American ginseng extract (Cold Fx®) has been licensed in 2007 as a natural health product to 'help reduce the frequency, severity and duration of cold and flu symptoms by boosting the immune system' with an estimated annual sale of over $48M [4,5]. Our findings on the paradoxical effects of AQ and PS extract on macrophage function in vivo may have significant implication in the use of American ginseng polysaccharides in several clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the polysaccharide fraction of ginseng has been shown to have immunomodulatory effects in both preclinical and clinical studies [3][4][5][6], although they are poorly characterized.…”
Section: Introductionmentioning
confidence: 99%